2017
DOI: 10.1038/s41598-017-09958-9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal umbilical cord blood transplantation halts skeletal disease progression in the murine model of MPS-I

Abstract: Umbilical cord blood (UCB) is a promising source of stem cells to use in early haematopoietic stem cell transplantation (HSCT) approaches for several genetic diseases that can be diagnosed at birth. Mucopolysaccharidosis type I (MPS-I) is a progressive multi-system disorder caused by deficiency of lysosomal enzyme α-L-iduronidase, and patients treated with allogeneic HSCT at the onset have improved outcome, suggesting to administer such therapy as early as possible. Given that the best characterized MPS-I muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Current postnatal treatments include costly, lifelong, immunogenic enzyme replacement therapy (ERT), and hematopoietic stem cell transplantation (HSCT), which is limited by donor availability, graft failure, graft-versus-host disease, and complications of myeloablation/immunosuppression 3 . Both human and mouse studies have demonstrated improved outcomes following early initiation of ERT or HSCT compared to late treatment [12][13][14][15][16] . Importantly, in humans, neither treatment resolves preexisting musculoskeletal and cardiac pathologies 3,4,13 , which significantly contribute to MPS-IH clinical grade 17 .…”
mentioning
confidence: 99%
“…Current postnatal treatments include costly, lifelong, immunogenic enzyme replacement therapy (ERT), and hematopoietic stem cell transplantation (HSCT), which is limited by donor availability, graft failure, graft-versus-host disease, and complications of myeloablation/immunosuppression 3 . Both human and mouse studies have demonstrated improved outcomes following early initiation of ERT or HSCT compared to late treatment [12][13][14][15][16] . Importantly, in humans, neither treatment resolves preexisting musculoskeletal and cardiac pathologies 3,4,13 , which significantly contribute to MPS-IH clinical grade 17 .…”
mentioning
confidence: 99%
“…Two studies on the effect of neonatal HSCT in MPS I mice reported almost complete prevention of bone disease 101,102 . A third study showed that after neonatal HSCT, MPS I mice had a significant improvement of parameters of bone structure and remodeling measured by μCT.…”
Section: Challenges In Treating Mps I Bone Disease: Emerging Therapiesmentioning
confidence: 99%
“…Furthermore, many available treatments have demonstrated their increased efficacy when started early in life, identifying age at treatment as a predictive factor for a better clinical outcome [ 156 , 158 , 165 , 183 , 184 , 185 , 194 , 263 , 264 ]. In particular, both experiences in animal models and MPSI patients showed an improvement in bone defects in cases of early treatments, considering ERT [ 184 ] and/or HSCT [ 265 , 266 , 267 ]. In view of this, a neonatal GT approach could be helpful because it allows for a very early treatment and, in parallel, it is associated with a reduced risk of immunological complications (i.e., immune response against the therapeutic enzyme).…”
Section: Therapeutic Options For Mpsi and Focus On Bone Limitationsmentioning
confidence: 99%